Numerical simulation of the wind flow around a tall building and its dynamic response to wind excitation - Revuz, Julia (2011)
Wind action is particularly important for tall buildings, both in providing a significant contribution to the dynamic overall loading on the structure and by affecting its serviceability. Whereas low and medium-rise buildings are fairly rigid, tall structures are characterized by a greater flexibility and a lower natural frequency, which is more likely to be in the frequency range of wind gusts. In addition, wake effects, such as vortex shedding, can become a significant problem for flexible structures when the vortex shedding frequency is close to the natural frequency of the building.